(untitled) (Bangladesh Journal of Medicine, 2023)
Background: Persistent COVID-19 symptoms and post-COVID chronic diseases have received more attention rather than the infection itself. This study’s goal was to evaluate the health status of recovered COVID-19 patients and analyze the factors associated with a high burden of symptoms. Methods: This was acohort study among hospital-released and recovered COVID-19 patients after three to six months of infection. Data was collected through a structured interview and analyzed by IBM SPSS (version25). Results: Fatigue (74.2%) followed by anxiety (38.9%) and joints paint (34.7%) were the most common symptoms of post-COVID period. Among participants, 21.34% had low dietary adherence and 17.2% had high adherence. A statistically significant correlation of high symptoms burden with dietary adherence and age was observed. People with low dietary adherence are at risk of high symptom burden and chronic diseases (AOR: 3.56, 95%CI:1.46-8.69). Habit of smoking, Asthma, Hypothyroidism, Ischemic heart disease are significant predictor (P<0.05). Patients those did not required ICU also had a lower risk of burden. Conclusion: Effective control of post- COVID symptoms is important to confirm a healthy life. Therefore, it is important to maintain good dietary practice, avoid bad habits and control of chronic diseases for a good quality of life. Bangladesh J Medicine 2023; 34(3): 214-222